Litter leachates have stronger impact than leaf litter on Folsomia candida fitness. (August 2020) - Chomel, Mathilde; Baldy, Virginie; Guittonny, Marie; Greff, Stephane; DesRochers, Annie
Abstract: It is well known that soil physico-chemical conditions and the nature of organic matter have important effects on soil micro-arthropod communities, including collembolans. However, mechanisms by which the physical or chemical quality of litter influence collembolan communities remain unclear. Plant secondary metabolites are partially released in soils through leaf and litter leaching and decomposition, and can have a strong influence on soil communities and their activity. In order to disentangle effects of the water-soluble compounds contained in the litter versus its physical effect, a microcosm experiment was set up exposing the collembola species Folsomia candida to either litter or litter leachates mixed to the substratum. Litter from three species with different chemical properties and one mixture (hybrid poplar, white spruce, grass and a mixture of poplar – spruce litter) and two concentrations of litter leachates (at 5% and 10% concentration) were used in microcosm experiments. After 30 days of incubation, reproduction and mortality rates of F. candida were assessed. Results showed that the tree litter leachates had a stronger impact on collembolan fitness compared to the litter itself, with a net reduction of survival and reproduction rates. Between 78 and 100% of mortality was observed in microcosms that received tree leachates, indicating a strong influence of the soluble compounds contained in tree leaves on collembolan. In contrast, collembolan reproduction was positively affected by the grass litter or 10% grass litter leachates compared to control (water). Our findings help to understand how chemical properties and leaf leaching may have important impacts on micro-arthropods communities and litter decomposition processes. Graphical abstract: Tree litter leachates increased mortality of Folsomia candida in comparison with the litter treatment or the controls, probably due to the solubility of secondary metabolites contained in the leaves and released in a free form in leachates. Image 1 Highlights: Tree litter leachates have stronger influence than litter itself on Folsomia candida fitness. Tree leachates have stronger effect on F. candida fitness than grass due to their content in secondary metabolites. Soluble phenolic compounds released by litter leaching can drive F. candida fitness. Litter compounds leaching appears to be an important process in aboveground-belowground interactions.